CHALLENGES FACING STUDENTS AND PARENTS IN THE DISTANCE LEARNING PROCESS: SYSTEMATIC REVIEW (American Journal of Pedagogical and Educational Research, 2025)
Distance learning has witnessed significant development in recent years, especially during the Covid-19 pandemic, which imposed the widespread adoption of this educational model. Despite the advantages it offers, such as flexibility and accessibility, students and parents face multiple challenges that affect the quality of education and the level of interaction. This study aims to systematically review the main challenges facing students and parents in the distance learning process, and classify them into technical, academic, psychological and social, and logistical axes. Technology is a crucial factor in the success of distance learning, but it also represents the most prominent challenges facing students and parents. Many families suffer from a lack of access to modern devices or fast internet networks, which hinders the continuity of learning. Some parents face difficulty in dealing with electronic educational platforms, which makes them unable to help their children effectively. Students suffer from psychological pressure due to the burden of academic tasks, while parents face pressure to provide an appropriate educational environment at home. The study highlights the importance of concerted efforts between governments, educational institutions, and parents to address challenges and make the most of distance learning as a modern educational tool.